Academic Research on the 2030 Agenda: Challenges of a Transdisciplinary Field of Study. Issue 3 (23rd January 2021) - Sianes, Antonio
Abstract: In 2015, the United Nations General Assembly formally adopted the 2030 Agenda for Sustainable Development, with the scope to shift the world on to a resilient path focused on promoting sustainable development leaving no one behind. Since the adoption of the 2030 Agenda, academic research on the topic has blossomed. However, most academic research has focused on specific topics within the Agenda, with a bias towards the 17 Sustainable Development Goals (SDGs) settled on it. The aim of this study is to contribute to the comprehension and delimitation of the 2030 Agenda as a field of study. To do so, we draw upon bibliometric techniques to undertake a sound analysis of the academic and thematic basis of the discipline, by analyzing the academic research on the Agenda to date, composed by 656 research papers. The results highlight the transdisciplinary nature of the 2030 Agenda, which has gathered attention from a wide range of disciplines and authors, especially in the sustainability and green sciences. At the same time, it points out some weaknesses in the development of a deeper comprehension of the 2030 Agenda from disciplines such as political and international sciences, which could hinder its governance, efficacy and impact. Abstract : We can foresee how certain topics, such as those linked to sustainability issues, are starting to follow a more scientific approach, and how traditional scientific fields such as health or violence, are being reinterpreted in light of the 2030 Agenda. However, in general, there is an overall tendency to write about the 2030 Agenda and not to deepen in the academic comprehension of its mechanisms.